Civil War on Sunday - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2000)
Jack and Annie are transported by their magic tree house to the time of the Civil War where they meet Clara Barton.
"A Stepping Stone book."
340
Accelerated Reader AR
Keywords: Barton, Clara, -- 1821-1912 -- Juvenile fiction; Time travel -- Juvenile fiction; Magic -- Juvenile fiction; Tree houses -- Juvenile fiction; United States -- History -- Civil War, 1861-1865 -- Juvenile fiction; Fantasy fiction; Historical fiction